EFL First-Year Students’ Writing Challenges and Strategies in the Transition from High School to University Writing - Ana Ahsana El Sulukiyyah; Utami Widiati; Francisca Maria Ivone; Sharmini Abdullah (JOALL (Journal of Applied Linguistics and Literature), 2026)
Writing at the university level presents significant challenges for EFL students. Although many studies have investigated EFL students’ academic writing challenges, few have focused specifically on paragraph writing, the foundational stage of academic writing development among first-year university students, particularly those transitioning from high school to university writing. Addressing this gap, this present study investigates students’ writing challenges, strategies, and their perceptions of differences and feedback. A total of 315 first-year Indonesian EFL students enrolled in the English study programs were selected through convenience sampling to complete a Likert-scale questionnaire adapted from the ESLP 82 Questionnaire. The findings reveal idea organization as the most prominent difficulty (M = 4.4; 83.5% agree), followed by issues of grammar and sentence structures (M = 4.3; 78.9% agree). Whereas, 85,7% students answered that university writing is more complex than high school writing activities, because it is needed a higher level of critical thinking, as 88,2% students acknowledged. As many as 80.8% students like to discuss with their teachers about their writing difficulties, and 89.5% prefer to use digital tools such as Grammarly and ChatGPT. At about 89,4% students stated that teacher feedback on grammar was considered helpful, but students rarely got peer feedback. These findings emphasize the urgent need for structured writing support that focuses on idea organization, grammar, vocabulary enhancement, and opportunities for peer interaction. To explore effective pedagogical interventions and the evolving role of digital tools in supporting academic writing development, further studies are highly recommended.